2022
DOI: 10.1186/s12951-022-01276-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic alteration of poroelastic attributes as determinant membrane nanorheology for endocytosis of organ specific targeted gold nanoparticles

Abstract: Background Efficacy of targeted drug delivery using nanoparticles relies on several factors including the uptake mechanisms such as phagocytosis, macropinocytosis, micropinocytosis and receptor mediated endocytosis. These mechanisms have been studied with respect to the alteration in signaling mechanisms, cellular morphology, and linear nanomechanical properties (NMPs). Commonly employed classical contact mechanics models to address cellular NMPs fail to address mesh like structure consisting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 82 publications
(97 reference statements)
0
13
0
Order By: Relevance
“…Atomic force microscope (AFM) has become an attractive characterization tool as it is a label free, non-invasive technique ideal for soft biological samples such as cells, tissues including the EVs [36][37][38]. The state-of-the-art technology allows for both morphological and nanomechanical characterizations of these samples in fluid environment, thus preserving their overall characteristics [39]. AFM has been used to evaluate the morphology of mesenchymal stem cell (MSC)-derived EVs ornated with LJM-3064 aptamer, a myelin-specific DNA aptamer on remyelination processes and immunomodulatory activity in myelin oligodendrocyte glycoprotein (MOG35-55)-induced mouse multiple sclerosis model [39].…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscope (AFM) has become an attractive characterization tool as it is a label free, non-invasive technique ideal for soft biological samples such as cells, tissues including the EVs [36][37][38]. The state-of-the-art technology allows for both morphological and nanomechanical characterizations of these samples in fluid environment, thus preserving their overall characteristics [39]. AFM has been used to evaluate the morphology of mesenchymal stem cell (MSC)-derived EVs ornated with LJM-3064 aptamer, a myelin-specific DNA aptamer on remyelination processes and immunomodulatory activity in myelin oligodendrocyte glycoprotein (MOG35-55)-induced mouse multiple sclerosis model [39].…”
Section: Introductionmentioning
confidence: 99%
“…18,22,23,25 The lipids not only play a passive role in hosting functional biomolecules but also play an active role in locally modulating the membrane mechanical properties in response to external stimuli and by being involved in adapting the molecular composition of both lipids and proteins to best support the needs of the cell. 26,27 It is therefore crucial to derive a comprehensive understanding of the nanomaterial−lipid interactions (i.e., adsorption, 12 desorption, 8 translocation, 28 and internalization/uptake 9,29 ) at the molecular level to achieve the desired application goal. Several experimental studies have outlined interactions between gold NPs (AuNPs) and model membranes, including their adsorption dynamics.…”
mentioning
confidence: 99%
“…In all of these systems, the approach often relies on mimicking the hydrophilicity profile of the membrane or finding ways to interact with or avoid specific cellular components (proteins, lysosomes, organelles, etc. ). The underlying challenge is to achieve control of the membrane–nanomaterials interactions, a task complicated by the large number of different biomolecules present in most biomembranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters cumulatively are used to quantify NPs of various biological entities (Kasas and Dietler, 2008;Redondo-Morata et al, 2014;Kenchappa et al, 2020). In our previous studies, we have shown the importance of optimizing the ramping parameters behind the acquisition of useful and informative F-S curves (Kulkarni et al, 2021;Kulkarni et al, 2022;Kulkarni et al, 2019a). In the present study, we exposed HUVECs to various durations of hypoxia (24, 48, 72 h) and performed nanoindentation using optimized ramping parameters.…”
Section: Hypoxia Induces Nanomechanical Alterations In the Membrane O...mentioning
confidence: 87%